Género masculino, cronicidad, bilateralidad, diagnóstico de panuveítis y/o enfermedad autoinmune como factores de riesgo asociados a complicaciones oculares en pacientes con uveítis. Instituto Regional de Oftalmología, 2012 - Ocupa Florian, Mario Antonio (2014)
To determine whether male gender, chronicity, bilateralism, the diagnosis of panuveitis and/or autoimmune disease are risk factors associated with ocular complications in patients with uveitis treated at the Regional Institute of Ophthalmology (IRO). 2012. Methodology: Analytical, observational, retrospective, case-control study. 409 medical records of patients diagnosed with uveitis in January-December 2012 were entered, constituting a study population of 310 that met the selection criteria, set to finally get by simple random sampling with random numbers table, 40 cases and 40 controls. Results: 50 (62.5 %) were men, the overall average age was 38.46 years (SD=16.3, range 6-70). Male gender [OR=0.3 , 95%CI (0.12-0.78) p<0.05], chronicity [OR=10.5 , 95%CI (3.4-32.5) p<0,01], bilateralism [OR=9.8 , 95%CI (1.2-82.1) p<0.05], diagnosis of panuveitis [OR=13 , 95%CI (1.6-107.2) p<0.05 ] and autoimmune disease [OR=5.3 , 95%CI (1.4-20.5) p<0.05] . Conclusions: Male gender is not a risk factor for complications of uveitis. Chronicity, bilateralism, the diagnosis of panuveitis and the presence of autoimmune disease are risk factors associated with ocular complications in patients with uveitis of the IRO. 2012